PENGEMBANGAN MEDIA PERMAINAN UNO STABAR MENGENAI PENCEGAHAN PENYAKIT DIABETES MELITUS TIPE 2 PADA REMAJA - Salsabila Fitria, Salma; Setiawan, Ridwan (Politeknik Kesehatan Kemenkes Bandung, 2024)
Background: Cases of DM (Diabetes Mellitus) in adolescents continue to grow. Preventive actions that can be taken in adolescence are by providing health information through health counseling regarding prevention that can be done by the adolescent age group to avoid DM disease, especially by consuming fruits and vegetables. Media development is needed to produce products according to the needs so that health education takes place effectively. The uno stacko fruit and vegetable game media is in accordance with the characteristics of adolescence because it can be played directly and done in groups. Objective: To develop Uno Stabar (Uno Stacko Fruit and Vegetable) game on the prevention of Diabetes Mellitus disease in adolescents at SMAN 1 Jalancagak with ADDIE model development research. Methodology: The type of research is R&D (Research and Develop). The population is 212 students of class XI MIPA SMAN 1 Jalancagak using proportionate random sampling technique. Results: Uno Stabar Game Media in the form of blocks with a size of 2.7 cm x 8 cm x 1.5 cm. obtained a score of 90.3% with a very feasible category from material experts, 81.3% with a very feasible category from media experts and 89% with a feasible category from small-scale trials. There is an effect of uno stacko fruit and vegetable game media with an increase of 60.06%. Conclusion: Uno Stabar Game Media is in the form of blocks, made of plastic, contains information on type 2 diabetes mellitus and cartoon images with color tones.